Recombinant Expression and Characterization of a New Laccase, Bioinformatically Identified, from the Antarctic Thermophilic Bacterium Geobacillus Sp. id17 - Cortés-Antiquera, R; Blamey-Alegria, J (Springer, 2023)
Geobacillus sp. ID17 is a gram-positive thermophilic bacterium isolated from Deception Island, Antarctica, which has shown to exhibit remarkable laccase activity in crude extract at high temperatures. A bioinformatic search using local databases led to the identification of three putative multicopper oxidase sequences in the genome of this microorganism. Sequence analysis revealed that one of those sequences contains the four-essential copper-binding sites present in other well characterized laccases. The gene encoding this sequence was cloned and overexpressed in Escherichia coli, partially purified and preliminary biochemically characterized. The resulting recombinant enzyme was recovered in active and soluble form, exhibiting optimum copper-dependent laccase activity at 55 °C, pH 6.5 with syringaldazine substrate, retaining over 60% of its activity after 1 h at 55 and 60 °C. In addition, this thermophilic enzyme is not affected by common inhibitors SDS, NaCl and l-cysteine. Furthermore, biodecolorization assays revealed that this laccase is capable of degrading 60% of malachite green, 54% of Congo red, and 52% of Remazol Brilliant Blue R, after 6 h at 55 °C with aid of ABTS as redox mediator. The observed properties of this enzyme and the relatively straightforward overexpression and partial purification of it could be of great interest for future biotechnology applications. © 2023, The Author(s), under exclusive licence to Springer Nature Japan KK, part of Springer Nature.